Laboratory assistant at mixed acid work bench (1920)
General view of a laboratory assistant, identified as "Mac May," posed at a work bench for mixed acid materials. Notably, the photograph is printed as a postcard, with space reserved on the verso for a message, mailing address, and postage. While the setting of this photograph is unidentified, inscriptions and supporting materials suggest that it many depict a laboratory associated with the U.S. Bureau of Standards. However, there is no contextual information directly linking this photo to the Bureau of Standards, which broadly conducted tests on a variety of physical materials, developed a range of technological standards, and supported the dissemination of scientific and technological information.
Keywords: Employees; Scientific apparatus and instruments; Postcards; Glassware; Laboratories